Analisis Kompetensi Pedagogik Dan Profesional Tutor Terhadap Hasil Belajar Warga Belajar Pendidikan Kesetaraan Paket C (Studi Pada Pusat Kegiatan Belajar Masyarakat Bahtera Dua Blitar) - Sumarlin Sumarlin; Imam Baehakki (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Tutor as one of the determinants of the success of educational goals and the spearhead of non-formal education are required to have competencies as an educator. The purpose of this study was to determine the significant effect of tutor’s pedagogical and professional competence in learning outcomes of education package equivalents C education in PKBM Bahtera Dua Blitar city 2017/2018. The population amounted to 160 people, with a sampel of 114 people consisting of residents learning the package C PKBM Bahtera Dua. Data collection methodhs used are questionnaire methods, interviews and documentation. The approach used is a quantitative approach using descriptive methods. The results of the study show that coefficient value f calculates pedagogic and professional competence has an effect on learning outcomes of learning groups learning packages C PKBM Bahtera Dua on Blitar city with probability values (sig. F change) = 0,000. Thus the hypothesis (ho) is rejected while hypothesis (ha) is minimized.